The Dynamics of Traditional Religion in the Political Economy of Ìkòrodú - Adéyẹmí Balógun (Yoruba Studies Review)
In the precolonial period, the coastal town of Ìkòrodú played a prominent role in the traffic of goods and services between traders on its coast and many Yorùbá groups who lived in the interior. While this traffic was sustained by socio-political institutions such as the Oloja and the Osugbo cult, the role of religious groups – including the Ifá priests, Màgbó, Líw`ẹ and Agẹmọ – remained highly influential because they represent the deities and spirits which shaped Ìkòrodú’s inhabitants’ views about social life, economic activities and political institutions. Ìkòrodú has, however, experienced a transformation from a traditional commercial economy into an urban center with modern industrial firms and capital infrastructures. The town has also witnessed the emergence of Muslim and Christian groups, and socio-ethnic groups from many parts of Nigeria. This transformation has not only challenged the authority of the traditional institutions in Ìkòrodú, it has also impacted on the religious beliefs and practices which underpin the socio-economic and political systems of the people. A notable example is the reduction in dates of religious festivals which Traditionalists believe were once instrumental in sustaining social order and prosperity in the town. The power of the state has also affected the responsibilities of the Traditionalists in the town. This article further shows how this transformation has shaped relations between religious groups and the state in Ìkòrodú.